The Signalled Licking/Avoidance of Punishment (SLAP) Paradigm in Rats: Capacity for Insight Between Goal Conditioning and Signalling Contingencies - Puzzo, Concetto; Oggiano, Maurizio; Capobianco, Micaela; Costa, Alberto; Pepe, Martina; Curcio, Giuseppe; De Laurenzi, Vincenzo; Laviola, Giovanni; Mannella, Francesco; Adriani, Walter (International journal of developmental neuroscience, 2025)
ABSTRACT In developmental‐age kids with specific‐learning‐disabilities (SLD), functional illiteracy entails poor logical reasoning; in those with attention‐deficit/hyperactivity disorder (ADHD), a deficit in prospective memory results in difficulty executing previously planned actions. We model this SLD and/or ADHD construct in the rat via the signalled‐licking/avoidance‐of‐punishment protocol (SLAP): We aim to study to assess rats' ability to merge two independently learned notions (one Pavlovian and one instrumental) and their deliberate exploitation. Rats were tested in Skinner boxes with a water‐dispenser and lickometer. The ‘Flash’ paradigm consists of 30‐min daily sessions, in which 5‐min safe phases (i.e., sound and light off, signalled free‐drinking) are intertwined by 1‐min unsafe phases (i.e., sound and light on). If subjects drink during unsafe phases, a mild footshock is released: Rats learn to withhold drinking. The ‘Allow’ paradigm starts and stays in the unsafe phase. Rats can shift to a 2‐min safe phase through a single nose poke in the active‐hole. The possibility to exert control over the environment, via seeking dark‐and‐silence (the predictive contingencies) as deliberate goal, is an unexplored construct in rats. In data from the ‘Flash’ paradigm, a greater number of licks/h during safe phases is confirming that rats easily understand classical passive‐avoidance contingencies. Findings from the ‘Allow’ paradigm indicate increased inefficacious nose pokes/h during safe phases, compared to unsafe ones. This is clearly suggesting that rats associate the change of phase with an outcome of their own input into the active nose‐poking device. However, rats do not understand the ‘potential’ for instrumental exploitation of their nose pokes. As such, no significant inferences were drawn across the two independent associative notions. Neurobiology of this putative ‘insight’ capability may rely on limbic‐striatal‐cortical networks. Impairments in the latter may be involved in deficits of prospective memory (in ADHD), and/or impairments in logic skills (in SLD). The SLAP protocol may offer insights on basic neurobiology as well as modulatory effects thereon of pharmacological molecules. The SLAP protocols run within a Skinnerbox apparatus. The environment includes an electrified grid floor that can deliver electric foot shocks (1.5 mA; 2 s), a speaker (emitter of sound with a frequency of 3000 Hz; 75 dB). Two nose poke devices on the side wall, a green nose poke cue within, a single white lamp in the centre of the front wall, and a water dispenser that is linked to a digital lickometer. Two protocols were run. The ‘Flash’ protocol consists in 1 min of unsafe phase (i.e., sound and light on during which the licking is punished by a footshock) followed by 5 min of safe phase (i.e., sound and light off, for signalled free drinking) and so on subjects cannot stop the unsafe phase and should just wait by withholding licks. The ‘Allow’ protocol starts with a 30‐min unsafe phase (signalled by sound and light). If subjects lick to drink water during this phase, they receive the electric foot shock. Rats can interrupt it and shift to a 2‐min safe phase: by means of a single nose poke, both light and sound are turned off, the green nose poke cue flashes and rats are signalled about a free drinking contingency.